Nicotinamide N-methyltransferase (NNMT): a novel therapeutic target for metabolic syndrome - Sun, Wei-Dong; Zhu, Xiao-Juan; Li, Jing-Jing; Mei, Ya-Zhong; Li, Wen-Song; Li, Jiang-Hua (Frontiers in Pharmacology, 2024)
Metabolic syndrome (MetS) represents a constellation of metabolic abnormalities, typified by obesity, hypertension, hyperglycemia, and hyperlipidemia. It stems from intricate dysregulations in metabolic pathways governing energy and substrate metabolism. While comprehending the precise etiological mechanisms of MetS remains challenging, evidence underscores the pivotal roles of aberrations in lipid metabolism and insulin resistance (IR) in its pathogenesis. Notably, nicotinamide N-methyltransferase (NNMT) has recently surfaced as a promising therapeutic target for addressing MetS. Single nucleotide variants in the NNMT gene are significantly correlated with disturbances in energy metabolism, obesity, type 2 diabetes (T2D), hyperlipidemia, and hypertension. Elevated NNMT gene expression is notably observed in the liver and white adipose tissue (WAT) of individuals with diabetic mice, obesity, and rats afflicted with MetS. Knockdown of NNMT elicits heightened energy expenditure in adipose and hepatic tissues, mitigates lipid accumulation, and enhances insulin sensitivity. NNMT catalyzes the methylation of nicotinamide (NAM) using S-adenosyl-methionine (SAM) as the donor methyl group, resulting in the formation of S-adenosyl-l-homocysteine (SAH) and methylnicotinamide (MNAM). This enzymatic process results in the depletion of NAM, a precursor of nicotinamide adenine dinucleotide (NAD + ), and the generation of SAH, a precursor of homocysteine (Hcy). Consequently, this cascade leads to reduced NAD + levels and elevated Hcy levels, implicating NNMT in the pathogenesis of MetS. Moreover, experimental studies employing RNA interference (RNAi) strategies and small molecule inhibitors targeting NNMT have underscored its potential as a therapeutic target for preventing or treating MetS-related diseases. Nonetheless, the precise mechanistic underpinnings remain elusive, and as of yet, clinical trials focusing on NNMT have not been documented. Therefore, further investigations are warranted to elucidate the intricate roles of NNMT in MetS and to develop targeted therapeutic interventions.